Onion yield as affected by plant density, nitrogen level and loss of leaf area - Siliquini, O. A. (2015)
Onion (Allium cepa) is an important horticulture crop because of its value as a food with a long shelf life being a relatively non-perishable product. It is very helpful to understand the growth response of the seeded onion crop to conduct appropriate field practices in attaining the highest or optimum yields. A three year field experiment was conducted using a variety of onion Valcatorce INTA, in a randomized block design with five replicates. Treatments were two plant densities and three rates of N application. The bulb growth followed a classical sigmoid curve. During the rapid growing period, the crop had the greatest leaf area (LA) with at least six leaves per plant. Increasing plant density increased yield in kg/ha, but decreased bulb size. Defoliating 40 to 60% of the LA had a significant impact on bulb production only at early growth stages. Late in the growing period, the remaining LA was apparently large enough for producing sufficient amounts of metabolites to feed new leaves, increasing their photosynthesis efficiency for the benefit of bulb production.